Layer generation in a stepless rapid prototyping system - Ngooi, Chan Siang. (2008)
Current rapid prototyping processes build parts in a layer by layer based on CAD data of a part that is either triangulated or sliced directly into thin layers representing consecutive cross-sections of the part. One of the problems is that side surfaces of a layer that are not perpendicular to the slice plane are approximated as vertical side surfaces, creating a staircase effect on the part surfaces. The aims of this thesis were to eliminate the staircase effect through a slanted layer building method to achieve higher rapid prototyping accuracy and to reduce the overall building time through thick layer deposition. A Stepless Rapid Prototyping (SRP) system is under development to fulfil these aims. A layer-slicing algorithm and a Layer Transfer Interface (LTI) data format were developed to create three-dimensional layers for slanted layer building. This new data format provides adaptive slicing of layers and hence enables a thick layer material deposition to support the use of these adaptive slices. An adaptive slicing on the de facto facet STL models was successfully carried out. To support the use of adaptive slicing, a powder sintering experiment on thermoplastic polymer layer of 1 mm thick was also examined. A sintering model was developed to predict the sintering time required for the thermoplastic powders used. Test parts were built and verified using both the SRP machine and Steoreolithography machine. Results showed that slanted layers with thick layer deposition were achieved in the SRP machine. This work suggests that the adaptive slicing of slanted layers on facet STL model and the corresponding thick layer deposition can be realized to achieve more accurate and faster rapid prototyping.